PEG-Functionalized Magnetite Nanoparticles for Modulation of Microbial Biofilms on Voice Prosthesis - Mara Caciandone; Adelina-Gabriela Niculescu; Aurelian Radu Roșu; Valentina Grumezescu; Irina Negut; Alina Maria Holban; Ovidiu Oprea; Bogdan Ștefan Vasile; Alexandra Cătălina Bîrcă; Alexandru Mihai Grumezescu; Miruna Silvia Stan; Alina Georgiana Anghel; et al. (MDPI AG, 2021)
This study reports the fabrication of nanostructured coatings based on magnetite, polyethyleneglycol, and biologically active molecule (polymyxin B-PM) for producing biofilm-resistant surfaces (voice prosthesis). Magnetite nanoparticles (MNPs) have been synthesized and functionalized using a co-precipitation method and were further deposited into thin coatings using the matrix-assisted pulsed laser evaporation (MAPLE) technique. The obtained nanoparticles and coatings were characterized by X-ray diffraction (XRD), thermogravimetric analysis with differential scanning calorimetry (TGA-DSC), scanning electron microscopy (SEM), transmission electron microscopy with selected area electron diffraction (TEM-SAED), Fourier-transform infrared spectroscopy (FT-IR), and infrared microscopy (IRM). Their antibiofilm activity was tested against relevant Staphylococcus aureus and Pseudomonas aeruginosa bacterial strains. The Fe3O4@PEG/PM surface of modified voice prosthesis sections reduced the number of CFU/mL up to four orders of magnitude in the case of S. aureus biofilm. A more significant inhibitory effect is noticed in the case of P. aeruginosa up to five folds. These results highlight the importance of new Fe3O4@PEG/PM in the biomedical field.